An Exploratory Study on Integrative Management of Irritable Bowel Syndrome with Constipation (IBS-C): Management of Irritable Bowel Syndrome with Constipation - Rajput, Izrum Shafi; Yawar, Warda; Ikram, Syeda Javeria; Zafar, Urooj; Jaffri, Muhammad Sajid Abbas; Zehra, Shabih (Pakistan Journal of Health Sciences, 2024)
Irritable Bowel Syndrome (IBS) was complicated disorder that results in pain and change in bowel habits. The major contributing factors to the onset and detoriation include stress and gastrointestinal problem. The women between 20 to 40 years were most commonly involved. The prevalence varies among countries that was affected by diet and diagnostic criteria. Objective: Compairing the efficacy of Mebeverine, Polyethylene Glycol with the combination therapy of Mebeverine and Polyethylene Glycol in Irritable Bowel Syndrome associated with Constipation. Methods: The comparative analytical study was conducted at the National Medical Centre, Karachi, and approved by the Ethical Review Committee of Bahria University Health Science Campus. Participants aged 15-50 with IBS were selected to reflect the target population. Observational data were collected based on the treatments they naturally received: Mebeverine, Polyethylene glycol, or a combination. Pain and constipation status were recorded at baseline (day 0) and after 24 days, analyzing the effectiveness of the treatments as they were administered in routine care settings. Results: The demographic data mentioned comparable age, weight, height, and gender distribution across the three groups. Constipation and pain status before and after varied considerably across the investigation time. There was substantial improvements by day 24 from the baseline in the combination therapy. Conclusions: The combination of Mebeverine and Polyethylene glycol reveals in managing IBS, with prominent improvements in constipation severity over the research duration. This highlights the importance of multimodal treatment methods in addressing the varied symptoms of IBS and enhancing the quality of life.